2021
DOI: 10.1097/md.0000000000027199
|View full text |Cite
|
Sign up to set email alerts
|

Removal of a catheter mount and heat-and-moisture exchanger improves hypercapnia in patients with acute respiratory distress syndrome

Abstract: To avoid ventilator-associated lung injury in acute respiratory distress syndrome (ARDS) treatment, respiratory management should be performed at a low tidal volume of 6 to 8 mL/kg and plateau pressure of ≤30 cmH 2 O. However, such lung-protective ventilation often results in hypercapnia, which is a risk factor for poor outcomes. The purpose of this study was to retrospectively evaluate the effectiveness and safety of the removal of a catheter mount (CM) and using heated humidifiers (HH)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Definition of hypercapnia and V T used among the included studies have been captured in Table 1 . A clear threshold for hypercapnia was reported in 11/29 of the included studies, that was defined as PaCO 2 ≥ 38 mmHg [ 19 ], PaCO 2 ≥ 45 mmHg [ 11 , 25 , 41 ], ≥ 48 mmHg [ 23 ], ≥ 50 mmHg [ 5 , 28 , 33 , 35 , 44 ] or ≥ 55 mmHg[ 34 ]. Information regarding V T were reported in all but three studies [ 5 , 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Definition of hypercapnia and V T used among the included studies have been captured in Table 1 . A clear threshold for hypercapnia was reported in 11/29 of the included studies, that was defined as PaCO 2 ≥ 38 mmHg [ 19 ], PaCO 2 ≥ 45 mmHg [ 11 , 25 , 41 ], ≥ 48 mmHg [ 23 ], ≥ 50 mmHg [ 5 , 28 , 33 , 35 , 44 ] or ≥ 55 mmHg[ 34 ]. Information regarding V T were reported in all but three studies [ 5 , 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…The typical symptom of acute respiratory distress syndrome (ARDS) is persistent hypoxemia, which often requires ventilation to correct hypoxemia. The ventilatory strategies can lead to hypercapnia [ 43 , 44 ]. It has been reported that in hypoxic adult rats, hypercapnia can induce IL-1β overproduction by activating nucleotide-binding oligomerization domain-like receptor protein 3 (NLRP3) inflammasome [ 45 , 46 ].…”
Section: The Role Of Pyroptosis and Autophagy In Microgliamentioning
confidence: 99%